Anisaatun Mursida KAJIAN KITAB ADABUL ALIM WAL MUTA’ALIM DALAM PEMBINAAN AKHLAK MENURUT KH HASYIM ASY’ARI: KAJIAN KITAB ADABUL ALIM WAL MUTA’ALIM DALAM PEMBINAAN AKHLAK MENURUT KH HASYIM ASY’ARI - Anisaatun Mursida; Khomsinnudin; Ubaidillah (STKIP Subang, 2026)
This study aims to examine in depth the content and moral education values contained in the book Adab al-‘Ālim wa al-Muta‘allim by KH. Hasyim Asy‘ari. This book is one of the intellectual heritages of pesantren that places morality (akhlaq) as the core of Islamic education. The research focuses on two main questions: (1) what is the content structure of the book Adab al-‘Ālim wa al-Muta‘allim; and (2) how are the values of moral education represented within it. The research employs a qualitative descriptive method with a library research approach. The primary data source is the original text of the book and its translation, while secondary data are obtained from relevant books, journals, articles, and previous studies. Data analysis is conducted using a descriptive-thematic technique by reading, classifying, and categorizing the book’s quotations into personal, social, and spiritual moral values. The findings show that the book consists of seven main sections discussing the virtues of knowledge, manners of students and teachers, etiquette toward books, ethics in discussions, choosing study partners, and the ideal traits of both teachers and students. The moral values identified include sincerity, patience, responsibility, discipline, humility, respect for teachers, polite communication, solidarity, love, mindfulness, trust in God (tawakkal), and self-purification (tazkiyah an-nafs). These values form an integrated character education system, in which personal morality strengthens social morality, and spiritual morality becomes the foundation of character formation. The study concludes that Adab al-‘Ālim wa al-Muta‘allim embodies Islamic educational principles relevant to addressing moral degradation in the modern era, serving as a valuable reference for character-based Islamic education curricula in both pesantren and formal education settings.